Research using population-based administration data integrated with longitudinal data in child protection settings: A systematic review - Chikwava, Fadzai; Cordier, Reinie; Ferrante, Anna; O'Donnell, M.; Speyer, Renee; Parsons, Lauren (PUBLIC LIBRARY SCIENCE, 2021)
Introduction: Over the past decade there has been a marked growth in the use of linked population administrative data for child protection research. This is the first systematic review of studies to report on research design and statistical methods used where population-based administrative data is integrated with longitudinal data in child protection settings.